How useful is routine pre-endoscopy viral screening? - Jemilohun, Abiodun Christopher; Elikwu, Charlse John; Ezuduemoih, Daniel Ekhaeyouno (International Journal of Infection Control, 2019)
Pre-procedural screening for hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV) are routinely done in several endoscopy centres in Nigeria. These tests constitute an additional layer of financial burden to the patients since most of them settle their medical bills out of pocket. At the same time, the burden of these viral infections on the society demands that all measures are taken to prevent their iatrogenic transmission. The aim of this study was to evaluate the prevalence of HBV, HCV and HIV among patients referred for gastrointestinal endoscopy so as to determine the relevance of routine screening before procedures. The study was a retrospective cross-sectional survey of patients referred to the Digestive Endoscopy Unit of the Babcock University Teaching Hospital, Ilisan-Remo, for endoscopy from January 2015 to December 2018. A total of 432 patients were included in the study. The mean age was 48.15 (±15.89) while the age range was 12-86 years. Of these, 240 (54.7%) were females while 199 (45.3%) were males. The results of the viral screening available in the record book varied: HBV (n = 419), HCV (n = 238) and HIV (n = 417). The prevalence of HBV, HCV and HIV was 4.3% (95% CI = 2.4% - 6.2%), 2.1% (95% CI = 0.4% - 4.2%) and 1.0% (95% CI = 0.2% - 1.9%) respectively. Fourteen (3.3%), 5 (2.2%) and 14 (3.4%) patients who were initially negative, were rescreened for HBV, HCV and HIV respectively for repeat endoscopy. None of these patients tested positive for the viruses. We found no evidence of viral transmission from endoscope to patients in our centre. Viral pre-screening for endoscopy in settings with low to moderate prevalence rates of HBV, HCV and HIV infections may not be necessary.